MENGELOLA CUSTOMER VOICE UNTUK MENINGKATKAN POSITIVE WORD OF MOUTH DAN MARKETING RESEARCH COOPERATION - Fatik Rahayu (Jurnal Manajemen., 2015)
Research examining the role of customer voice to encourage positive word ofmouth and marketing research cooperation in higher education service is scarce. This paper aims to examine the antecedents and consequences of customer voice within a higher education context. A qustionnaire was developed with item measures that captures the constructs in the conceptual model. A survey of higher education student was undertaken. The data are analysed with SEM. The result show there is a significant impact of prior complain experience and attitude toward complain on customer voice. And the customer voice have impact on positive word of mouth and marketing research cooperation.